2000
DOI: 10.1182/blood.v95.4.1427.004k48_1427_1434
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of leukemic cells accompanies reduction in intracellular pH after targeted inhibition of the Na+/H+exchanger

Abstract: The Na+/H+ exchanger isoform 1 (NHE1) is primarily responsible for the regulation of intracellular pH (pHi). It is a ubiquitous, amiloride-sensitive, growth factor–activatable exchanger whose role has been implicated in cell-cycle regulation, apoptosis, and neoplasia. Here we demonstrate that leukemic cell lines and peripheral blood from primary patient leukemic samples exhibit a constitutively and statistically higher pHi than normal hematopoietic tissue. We then show that a direct correlation exists between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
84
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(96 citation statements)
references
References 40 publications
8
84
0
4
Order By: Relevance
“…KS Park et al minimizes NHE activity (Slepkov et al, 2007). The apoptotic effects of amiloride analogues observed in this condition thus cannot be attributed to the intracellular acidification resulting from NHE inhibition, as previously suggested (Rich et al, 2000). In liver cells, apoptosis induced by NHE inhibitors is associated with activation of JNK kinase (Suzuki and Tsukamoto, 2004) or with the inhibition of ERK kinase (Konstantinidis et al, 2006).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…KS Park et al minimizes NHE activity (Slepkov et al, 2007). The apoptotic effects of amiloride analogues observed in this condition thus cannot be attributed to the intracellular acidification resulting from NHE inhibition, as previously suggested (Rich et al, 2000). In liver cells, apoptosis induced by NHE inhibitors is associated with activation of JNK kinase (Suzuki and Tsukamoto, 2004) or with the inhibition of ERK kinase (Konstantinidis et al, 2006).…”
Section: Discussionmentioning
confidence: 54%
“…In contrast to their protective effects, amiloride derivatives also elicit growth inhibition and apoptotic cell death in hepatocytes (Suzuki and Tsukamoto, 2004), leukaemic cells (Rich et al, 2000), smooth muscle (Chen and O'Brien, 2003) and neurons (Schneider et al, 2004). Based on these apoptotic effects, amiloride analogues were proposed as potential therapeutic agents against metastasis and multi-drug resistant cancers (Harguindey and Cragoe, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in pH i was shown to be an essential prerequisite for DNA synthesis, cell proliferation, and activation of glycolysis (Grinstein et al, 1989). Recently, Rich et al (2000) described a pH i approximately 0.4 units higher in various leukemia cell lines as compared to peripheral blood mononuclear cells (PBMC) from healthy donors. Importantly, they demonstrated that leukemia cells from patients also possess a more alkaline pH i than do PBMC from healthy donors suggesting an essential function of elevated pH i in tumor cells (Rich et al, 2000).…”
mentioning
confidence: 99%
“…Recently, Rich et al (2000) described a pH i approximately 0.4 units higher in various leukemia cell lines as compared to peripheral blood mononuclear cells (PBMC) from healthy donors. Importantly, they demonstrated that leukemia cells from patients also possess a more alkaline pH i than do PBMC from healthy donors suggesting an essential function of elevated pH i in tumor cells (Rich et al, 2000). Further support for this hypothesis was found after transformation of NIH-3T3 cells by the E7 oncogene from human papilloma virus-16.…”
mentioning
confidence: 99%